A produção do espaço urbano em Pau dos Ferros: uma análise da produção fundiária e imobiliária - Nunes, Hugo Leonardo Pontes (2024)
Debates regarding the production of urban space are important in discussions about cities. The theme is relevant, as it is capable of contextualizing and identifying processes of urban transformation, the agents involved and their contributions to the reality of a given location. Within this theme, this research was carried out in Pau dos Ferros, a city with 30,479 inhabitants, located in the interior of Rio Grande do Norte, approximately 400km from the state capital, Natal. The research aimed to understand its production of urban space by analyzing issues involving land and real estate production in the city, going through the process of transforming rural/semi-rural into urban, mapping of constructions, pricing and who were the determining agents in this period. The production time frame was from 2009 to 2023, a time in which this growth was intensified by the arrival of important public institutions in the city. Finally, the research sought to understand how the state acted with regard to urban planning during this period, through the municipal sphere. Through a quantitative approach containing field research to obtain data, an intense movement in the real estate market in the city was identified, with more than 3,000 works in the time frame that comprises the work, in addition to an expansion zone with valued land and new construction typologies in buildings. It was also possible to understand that the processes that occurred were shaped by land owners and real estate developers, without due monitoring by the municipal sphere in urban planning, in a period that marked an intensification in the city's urban expansion